(untitled) (Journal of Research Administration, 2023)
Drug addiction is a complex phenomenon characterized by a compulsive use of substances that affects the human mind and body. It is often affected by genetic, environmental, and psychological factors. However, it is not merely a moral failure, rather it is a chronic disorder and it requires a comprehensive understanding and compassionate response to recover. To maintain a healthy social context, it is important to eradicate social illnesses like drug addiction. The ethical degradation of any society is greatly affected by the serious social issues like drug addiction, alcoholism, juvenile delinquency and so on. Previous studies approached the topic from a macro perspective paying nominal attention to micro view of the issue. Hence in this study an attempt has been made to approach the subject from the victim’s point of view staying at the rehabilitation center for their recovery. It is a qualitative research based on both primary and secondary data. This study focuses on understanding the reason for drug addiction and remedial measures provided to them by the concerned authorities. It is a study to discuss the different aspects related to drug addiction with special reference to a rehabilitation centre. The study also investigates the status of Govt policies to eradicate drug addiction. Thus, the study helps to know the causes and remedies of drug addiction, and the responses of competent authorities in this regard. The study found the maximum number of drug addicts are due to psychological and family environments. It is suggested to create a supportive environment for the speedy recovery of the drug addicts. Keywords: Drug Addiction, Recovery, Rehabilitation, Treatment, Substance Abuse, Govt Policies